Kelompok Dukungan Sebaya berhubungan dengan Kualitas Hidup Orang dengan HIV/AIDS - Sekar Ayuningtyas; Sugih Wijayati; Muhamad Jauhar (JURNAL KEPERAWATAN RAFLESIA, 2021)
The phenomenon of HIV / AIDS has an impact on the national stablity. The factors is risky sexual behavior and drugs. The impact is a community stigma that affects the quality of life of people living with HIV/AIDS (PLWHA). Peer group support can improve the quality of life of PLWHA. This study aims to determine the relationship between peer group support and the quality of life of PLWHA. This study used an analytic observation design with a cross sectional approach. The study used simple random sampling. A sample of 62 clients in the Peer Support Group (KDS) Arjuna Plus Semarang. The study used a peer group support questionnaire (validity value 0.335-0.708 and reliability 0.426) and quality of life (validity value 0.325-0.602 and reliability 0.582). Data analysis using Pearson product moment correlation test. The mean ageof PLWHA is 33.56 years, male (62.9%), high school (40.3%), private employees (75.8%). There was a significant relationship between peer group support and quality of life among PLWHA (p value = 0.045). Peer group support is related to the quality of life of PLWHA. Nurses as a health service providers collaborate with Peer Support Groups in improving the quality of life of PLWHA.